2007
DOI: 10.1021/bi602547m
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid as a Directly Binding Activator of the Insulin Receptor:  Protection from Hepatocyte Apoptosis

Abstract: Alpha-lipoic acid mediates its antiapoptotic action via activation of the insulin receptor/PI3-kinase/Akt pathway. We show for the first time a direct binding site for alpha-lipoic acid at the insulin receptor tyrosine kinase domain, which might make alpha-lipoic acid a model substance for the development of insulin mimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 37 publications
(53 reference statements)
2
45
1
1
Order By: Relevance
“…Similar results have only recently been found in hepatocytes, where inhibition of apoptosis by ␣-lipoic acid as well is associated with activation of the PI 3-kinase/Akt pathway (18).…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have only recently been found in hepatocytes, where inhibition of apoptosis by ␣-lipoic acid as well is associated with activation of the PI 3-kinase/Akt pathway (18).…”
Section: Discussionsupporting
confidence: 85%
“…In this regard, we have demonstrated for the first time that LA prevents degradation of IRS proteins induced by PA. In a previous study, it was shown that the protection of LA against TNFĮ/actinomycin D-mediated apoptosis was due to a direct activation of the IR [83].…”
Section: Discussionmentioning
confidence: 99%
“…23 Regarding the other examined proteins (1ZSX, 1Q5M and 1CQZ), not all CP-CIE values were negative, and consequently, the interactions are not totally favorable, although the affinity value calculated for 1ZSX was the same as that obtained for 1HS6.…”
Section: Resultsmentioning
confidence: 78%
“…[20][21][22] The biochemical importance of ALA is mainly represented by its participation as a cofactor in several biological processes, and due to its antiapoptotic action via activation of the insulin receptor/PI3-kinase/Akt pathway. 23 Nowadays, in silico screening has made possible to find suitable biological targets for particular compounds. Target Fishing Dock (TarFisDock) is a web server that docks small molecules with protein structures in the Potential Drug Target Database (PDTD), as a tool to discover new drug targets.…”
Section: -16mentioning
confidence: 99%